Comparison of Carbon Footprint of Organic and Conventional Farming of Chinese Kale - Yuttitham, Monthira (Environment and Natural Resources Journal, 2018)
This study compared the carbon footprint (CF) of organic agriculture with that of conventional agriculture in the cultivation of Chinese kale. The farm management data collected included the use of chemical and organic fertilizers, and fossil fuel for tillage, irrigation and transportation. Greenhouse gas emissions (GHG) were calculated and added to the CF. The results showed that conventional agriculture had a CF of 0.402±0.47 kg CO2e/kg Chinese kale. Proportion of CFs from: chemical fertilizer (51%), transportation (21%), irrigation (19%), tillage (5%), organic fertilizer (2%), herbicide (1%) and insecticide (1%), and organic agriculture had a CF of 0.195±0.122 kg carbon dioxide CO2e/kg Chinese kale (proportion of CFs from: transportation (81%) organic fertilizer (12%) and fossil fuel for irrigation (7%). The CFs differed, depending on farm management, and that of conventional agriculture was almost double that of organic agriculture because of the higher emissions from use of chemical fertilizers and of fossil fuel for tillage, herbicide and insecticide applications. The conventional farm management led to higher production per unit of planted area. Thus, it seems that conventional farming has relatively higher CF than organic farming. There is still room for both management practices to reduce their GHG emissions and their CFs by reduce chemical fertilizer and fossil fuel use in conventional farming. The promotion of organic farming practices will help to improve sustainable, environmentally friendly agricultural production of Chinese kale in Thailand.